Perkembangan Bahasa Indonesia pada Era Teknologi Informasi dan Komunikasi - Sutisno Adam (Kantor Bahasa Provinsi Maluku Utara, 2015)
Language is dynamic, it evolved along with the development of human civilization . This is no exception in the Indonesian language is the national language and unifying the people of Indonesia . In the era of Information and Communication Technology (Information and Communication Technology) today, this language Indonesia experienced a rapid development. These developments triggered fundamental changes in the body besides Indonesian who had a positive impact also have negative impacts which is crucial in the process of preservation Indonesian existence in the future.